2022
DOI: 10.1161/jaha.121.022865
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Complexity Discriminates Pathological Beat‐to‐Beat Variability as a Marker of Vascular Aging

Abstract: Background Beat‐to‐beat blood pressure variability (BPV) is associated with an increased risk of stroke but can be driven by both healthy physiological processes and failure of compensatory mechanisms. Blood pressure (BP) complexity measures structured, organized variations in BP, as opposed to random fluctuations, and its reduction may therefore identify pathological beat‐to‐beat BPV. Methods and Results In the prospective, population‐ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The non-linear measures of BPV, multiscale entropy shows its potential in revealing the blood pressure variations at different time scales or frequencies [ 51 , 97 ]. BP regulation involves various elements, including cardiac output, vascular resistance, and neural and hormonal feedback mechanisms, all operating at different time scales.…”
Section: Discussionmentioning
confidence: 99%
“…The non-linear measures of BPV, multiscale entropy shows its potential in revealing the blood pressure variations at different time scales or frequencies [ 51 , 97 ]. BP regulation involves various elements, including cardiac output, vascular resistance, and neural and hormonal feedback mechanisms, all operating at different time scales.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should examine mechanisms such as cardiac output, vasomotor activity, baroreflex sensitivity, and breathing contributions to the changes in BTB BPV during HIIE. (2, 8, 53, 54) Autonomic dysfunction in various other populations such as diabetes and heart failure may also respond to HIIE differently and provide clinical insights about the cardiovascular and autonomic function interaction. (5557) Our analysis performed low volume HIIE, however future studies could examine effects of short and long interval HIIE which would provide different stimulus to factors that alter the BTB BPV response.…”
Section: Future Considerationsmentioning
confidence: 99%
“… 16. Variability in neuro-cardiovascular regulatory mechanisms : Using fractal methods on data extracted from wearable devices to quantify the variability in fluctuating daily physical activity patterns has shown that aging and mortality were associated with decreased variability ( Raichlen et al, 2019 ; Bencivenga et al, 2022 ; Lee et al, 2022 ). Physiological complexity was proposed as a biomarker of aging, and interventions that aim to regain complexity in physical activity might slow the aging process.…”
Section: The Hallmarks Of Aging Are Associated With Variability: Inte...mentioning
confidence: 99%
“…The correlation between aging and the variability or entropy of different cardiovascular parameters, including systolic and diastolic blood pressure, heart rate, and oxygenated hemoglobin, was examined in several studies. Some of these have demonstrated reduced variability with aging or frailty, while others have shown the reverse association ( Fukusaki et al, 2000 ; Viola et al, 2011 ; Nemati et al, 2013 ; Toosizadeh et al, 2022 ; Ogliari et al, 2016 ; Knight et al, 2020 ; Lee et al, 2022 ).…”
Section: The Constrained Disorder Principle Defines Aging As Moving O...mentioning
confidence: 99%